Estrés laboral y salud física y mental en los trabajadores de la Unidad de Ambulatoria IESS-Machachi. Diseño de un programa de salud mental para la institución. - Barba Gallardo, Pablo Andrés (2015)
In this research work, the various physical and psychological changes that are due to work stress in the hospital setting were evaluated, exploring the link between job stress with psychological, emotional and physical well-being of health workers. In the public health is vital to design health systems and programs, both mentally and physically, to help the workers' welfare from different areas which are considered vulnerable to this problem, health has been one of the most controversial areas since there is no empowerment of this situation because of the carelessness of the medical staff and their supposed mysticism about the stressful conditions. The main objective has been the development of a mental health program with psychological solving strategies to fight the stress problems based on the "MASLACH" method. The study was conducted on a population of 16 health professionals in the Ambulatory Care Unit IESS-Machachi, on which two fundamental facts were concluded: the first one is that there are high and middle levels of significant stress, considering that doctors are the professionals who have a high predisposition to generate this problem in their working lives, and the second is that there are the psychological symptoms and behavioral levels which were evident in the interviews; also it is evident the minor attention to this phenomenon which brings consequences in their health. The solution to this situation is to give health professionals of the unit a new material that includes a collection of various psychophysical methods that help to reduce the symptoms and disorders of silent stress.